WU BRADING, Celia (Introducción, Recopilación e Ilustraciones). Testimonios Británicos de la ocupación chilena de Lima; Edit. Milla Batres, Lima, 1986; 158 pp. - Pons Muzzo Díaz, María Elsa (Histórica, 1987)
No contiene resumen